Suprascapular nerve entrapment in young kayaker: a case report - LiBrizzi, C. L.; Rojas, J. L.; Bontrager, N. C.; Srikumaran, U.; McFarland, E. G. (The Physician and Sportsmedicine, 2020)
Kayaking has become one of the most popular paddle sports throughout the world. The shoulder is the most commonly injured area of the body among kayaking participants as a result of acute traumatic events and chronic overuse injuries. Therefore, kayaking participants may often seek advice for shoulder problems and there is a scarcity of studies regarding shoulder injuries in this population. In this case report, we present a young male recreational whitewater kayaker with a severe suprascapular nerve (SSN) entrapment who presented with shoulder pain and inability to perform his sport. He was initially evaluated elsewhere and was treated with nonsteroidal anti-inflammatory medications and physical therapy for presumptive diagnosis of subacromial impingement. After 5 months of failed non-operative treatment, the patient sought a second opinion with our group. SSN entrapment diagnosis was confirmed by a thorough careful physical examination, magnetic resonance imaging and electrodiagnostic study. Given the failure of non-operative treatment, the patient was treated with arthroscopic SSN decompression and successfully returned to kayaking without symptoms. While SSN entrapment has been reported in a variety of sports, especially those involving overhead movements, this is the first case report of SSN entrapment reported which impaired participation in kayaking. This case report supports the consideration of SSN entrapment in the differential diagnosis of painful shoulder among kayaking participants and highlights the importance of undressing the patient and examining the posterior shoulder for atrophy, winging or deformity.